Supervised, but Not Home-Based, Isometric Training Improves Brachial and Central Blood Pressure in Medicated Hypertensive Patients: A Randomized Controlled Trial - Farah, Breno Q.; Rodrigues, Sergio L. C.; Silva, Gustavo O.; Pedrosa, Rodrigo P.; Correia, Marilia A.; Barros, Mauro V. G.; Deminice, Rafael; Marinello, Poliana C.; Smart, Neil A.; Vianna, Lauro C.; Ritti-Dias, Raphael M. (Frontiers in Physiology, 2018)
Background: The purpose of this study was to compare the effects of supervised and home-based isometric handgrip training on cardiovascular parameters in hypertensives. Methods: In this randomized controlled trial, 72 hypertensive individuals (58±2 years old, 70% female) were randomly assigned to three groups: home-based, supervised isometric handgrip training or control group. Home-based and supervised isometric handgrip training was completed thrice weekly (4x2 minute at 30% of maximal voluntary contraction, with 1-minute rest between bouts alternating the hands). Before and after 12 weeks after the isometric handgrip intervention office, central and ambulatory blood pressures (BP), arterial stiffness, heart rate variability, vascular function, oxidative stress and inflammation markers were obtained. Results: No significant (p>0.05) effect was observed for ambulatory BP, arterial stiffness, heart rate variability, vascular function and oxidative stress and inflammation marker in all three groups. Office BP decreased in the supervised group (Systolic: 132±4vs.120±3mmHg; Diastolic: 71±2vs.66±2mmHg, p<0.05), whereas no significant difference was observed in the home-based and control groups (Systolic: 130±4vs.126±3; diastolic: 73±3vs.71±3 mmHg, p>0.05) add control data here. Supervised handgrip exercise also reduced central BP systolic (120±5vs.109±5 mmHg), diastolic (73±2vs.67±2 mmHg); and mean BP (93±3vs.84±3 mmHg), whereas no significant effect was found in the home-based (Systolic:119±4vs.115±3; Diastolic: 74±3vs.71±3) and control groups (p>0.05). Conclusion: Supervised, but not home-based, isometric training lowered office and central BP in hypertensives.